Indonesia : Economic and Social Update, October 2005 - World Bank (Washington, DC, 2021)
This October 2005 edition of the Indonesia economic and social update reports that the government moved to address ballooning fuel subsidies and exchange rate instability with a bold policy package. The report emphasizes the importance of a good macroeconomic policy, investment climate reforms, and effective expenditure management in Indonesia, comprising a continued focus on reducing the government debt burden (as measured by a trend decline in debt to GDP), and depoliticizing domestic fuel prices by linking them to international prices and monetary policy designed to bring inflation in line with regional averages. It also urged that a clear articulation and coordination of policy announcements be a priority. Improvements to the investment climate would be led by reversing the slide in oil and gas exploration and production, concrete measures to address investor concerns including the time and expense to register a company and redressing cumbersome tax administration procedures. A quick clearance of an investment bill that dramatically reduced red tape would send out a strong, highly visible signal to investors. However, the report notes that Indonesia's key challenge may lie in the allocation and management of public expenditures. The government's reduction of untargeted fuel subsidies and their reallocation to capital and social spending represent an unprecedented opportunity to improve the level and quality of growth in the medium term. The government will need to build on budget reforms to improve the link between government priorities (accelerating infrastructure and reducing poverty, for example), improving the efficiency of budget procedures, and reducing leakages.